2018
DOI: 10.3390/ijerph15112565
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Coal Workers’ Lung Diseases: A Comparative Analysis of China, Australia, and the United States

Abstract: China has high and increasing annual rates of occupational lung diseases such as pneumoconiosis and silicosis. In contrast, Australia and the United States of America (USA) have greatly lowered their annual rates of lung diseases since the 1970s. This paper systematically compared and analysed the multi-elements of coal dust management and health management in these three countries to provide a reference for China. Regarding coal dust management, this paper found that coal workers in China are more susceptible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…In contrast, in New Zealand, Taiwan (China) and Montenegro, there has been an increasing trend. Government-based operations and progressive coal mining companies have recently chosen to put more energy and money into production safety with respect to trade-offs between ‘visible and immediate accidents’ and ‘invisible and chronic lung diseases’, which can seriously damage coal miners’ lives and health 27–30…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in New Zealand, Taiwan (China) and Montenegro, there has been an increasing trend. Government-based operations and progressive coal mining companies have recently chosen to put more energy and money into production safety with respect to trade-offs between ‘visible and immediate accidents’ and ‘invisible and chronic lung diseases’, which can seriously damage coal miners’ lives and health 27–30…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in New Zealand, Taiwan (China), and Montenegro, there has been an increasing trend. Government and coal mines choose to put more energy and money into production safety in the trade-off between "visible and immediate accidents" and "invisible and chronic lung diseases", which seriously damages coal miners' lives and health, and restricts the healthy development of the coal industry [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 2015 revealed that the prevalence of silicosis in South African gold miners kept a relatively high level between 1984 and 2009, and in India, an estimated 11.5 million workers are still exposing to silica dust . In China, more than half a million silicotic cases were diagnosed between 1991 and 1995, of whom 24 000 silicosis‐related deaths occurred annually . Thus, silicosis is still a severe global health problem, especially in developing or undeveloped countries.…”
Section: Introductionmentioning
confidence: 99%